2015
DOI: 10.1002/qj.2527
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the regional Arctic System Reanalysis and the global ERA‐Interim Reanalysis for the Arctic

Abstract: • N demonstrate smaller precipitation biases in the ASRv1 than the ERAI except during the summer, when the ASRv1 is very dry. Short-wave radiation compared with observations is much too large in the ASRv1, and both reanalyses show long-wave radiation deficits during most months. These results point to inadequacies in model physics in the ASRv1 (e.g. convective and radiation schemes) that will continue to be refined in subsequent versions of the ASR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 69 publications
2
142
0
1
Order By: Relevance
“…As a follow up of this study, it would be interesting to investigate the causes of the missing high values of fluctuating velocities and the overestimation of the integral timescale, first by examining the impact of the atmospheric forcing resolution and second by checking how the inertial/tidal oscillations are represented by the two modeling platforms used here. To better asses the quality of the simulated sea-ice dynamics, it would be interesting to also perform a dispersion analysis as in Rampal et al (2008) or to specifically study sea-ice deformation as in Bouillon and Rampal (2015) with data from models and observations. Finally, it is worth noting that the representation of the mean sea-ice circulation depends on many processes (mean circulation of the atmosphere and ocean, spatial and temporal variation of the ocean-ice and air-ice drag coefficients as a function of the ice age/type, representation of the ocean-ice and atmosphere-ice boundary layers (McPhee, 2012), etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a follow up of this study, it would be interesting to investigate the causes of the missing high values of fluctuating velocities and the overestimation of the integral timescale, first by examining the impact of the atmospheric forcing resolution and second by checking how the inertial/tidal oscillations are represented by the two modeling platforms used here. To better asses the quality of the simulated sea-ice dynamics, it would be interesting to also perform a dispersion analysis as in Rampal et al (2008) or to specifically study sea-ice deformation as in Bouillon and Rampal (2015) with data from models and observations. Finally, it is worth noting that the representation of the mean sea-ice circulation depends on many processes (mean circulation of the atmosphere and ocean, spatial and temporal variation of the ocean-ice and air-ice drag coefficients as a function of the ice age/type, representation of the ocean-ice and atmosphere-ice boundary layers (McPhee, 2012), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Using such approaches to simulate the spread of sea ice would be inappropriate because sea-ice motion fields are intermittent in time and discontinuous in space, but are valid for reproducing the statistics of individual sea-ice trajectories. The "random walk" model was, for example, used in Colony and Thorndike (1985) with a mean field and statistics on the fluctuations derived by Colony and Thorndike (1984).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature difference, T a − T s is taken between the ice surface and the atmosphere at 2 m, the same as the difference in specific humidity, q a − q s . We calculate the specific humidity using the formulation of Buck (1981). The drag coefficients C t and C q are set to 1.3 × 10 −3…”
Section: Thermodynamical Componentmentioning
confidence: 99%
“…After adding the extra 10-m level, we find that on average there are eight or nine levels located below 1500 m. We analyse the 11-year period from 2000 to 2010 but we only consider winter months (October-March). Bromwich et al (2015) compared the near-surface and upper-level analyses from ASR-Interim and ERA-Interim with surface station data and soundings made in the Arctic region. They found that the correlation between the observed and analysed 10-m wind speed was higher in ASR-Interim than in ERA-Interim during every month (during winter months the correlation for ASR-Interim was 0.72 and for ERA-Interim 0.67) and that ASR-Interim showed slightly negative bias whereas ERA-Interim showed positive bias.…”
Section: Arctic System Reanalysis -Interim Data Setmentioning
confidence: 99%